Staff experience of harassment and stalking behaviour by patients - Clarke, Martin; Yanson, Ian; Saleem, Younis; Edworthy, Rachel; Khalifa, Najat (Taylor & Francis, 2016)
Staff from one National Health Service (NHS) Trust in England completed an online survey (N = 590) about their experience of intrusive behaviours from patients. These experiences were categorised into either stalking or harassment and compared in terms of staff and patient characteristics, types of intrusions, and aftermath. Overall, 150 were classified as being stalked (25.4%) and 172 harassed (29.2%). There were no differences in staff characteristics between the two groups. Staff from forensic services and nursing staff were particularly susceptible to these intrusions which took many forms. Respondents perceived a range of causes for the stalking and harassment, the most common being to gain power and control/to scare. It was rare for legal sanctions to be brought against the patient. Our findings reinforce the need for service providers to have policies supported with preventative measures, education and a robust process for addressing stalking so that these measures are embedded in practice in a way that supports staff working with patients. Furthermore, service providers should be challenged on what steps they have taken to prevent, and monitor, such behaviour.